The Shadow State: Why Babita Deokaran Had to Die (Jeff Wicks) - Solomon, Hussein (Scientia Militaria - South African Journal of Military Studies, 2025)
The Shadow State: Why Babita Deokaran Had to Die by Jeff Wicks, Cape Town: Tafelberg, 2025, 256 pages, ISBN 978-0-6240-9494-4.